Unemployment, commuting, and search intensity - Matthias Wrede (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institut für Wirtschaftspolitik und Quantitative Wirtschaftsforschung (IWQW), 2011)
Employing a standard matching unemployment model extended by within-labor-market-regions commuting, this paper analyzes the tradeoff between commuting costs and unemployment. Depending on whether commuters are able to bargain for fringe benefits, search may or may not be biased towards distant workplaces and less productive centers. As a consequence, unemployment benefits should be tied to search in high productivity regions. Using German county data, the paper tests some positive predictions that emerge from of the model. In particular, it confirms that increasing labor market tightness reduces the willingness to out-commute.
Keywords: R12; R13; R14; H22; 330; unemployment; matching; commuting; search; labor market policy